Genetic susceptibility to bortezomib-induced peripheral neuroropathy: replication of the reported candidate susceptibility loci - Campo, Chiara; Weinhold, Niels; Goldschmidt, Hartmut; Merz, Maximilian (Neurochemical research, 2016)
The introduction of proteasome inhibitors in the treatment of multiple myeloma (MM) patients has been a therapeutic success. Peripheral neuropathy (PNP) remains one of the most frequent side-effects experienced by patients who receive these novel agents. Recent investigations on the mechanisms of PNP in patients treated with bortezomib have suggested genetic susceptibility to neurotoxicity. We used data from a genome-wide association study conducted on 646 bortezomib-treated German MM patients to replicate the previously reported associations between single-nucleotide polymorphisms (SNPs) in candidate genes and PNP in MM patients, including 298 SNPs with a nominal significance (p value <0.05). Twelve associations were confirmed at a significance level p value <0.05. The corresponding SNPs are located in genes involved in drug metabolism (ABCC1, ABCC6), development and function of the nervous system (POGZ, NFAT pathway, EDN1), modulation of immune responses (IL17RD, IL10RA) and the NF-κB signaling pathway (PSMB4, BTCR, F2). We systematically investigated functional consequences of those variants using several bioinformatics tools, such as HaploRegV4.1, RegulomeDB and UCSC Genome Browser. Expression quantitative trait loci (eQTL) data suggested that some of the identified SNPs might influence gene expression through a differential recruitment of transcription factors. In conclusion, we confirmed some of the recently reported associations between germline variation and PNP. Elucidating the mechanisms underlying these associations will contribute to the development of new strategies for the prevention or reduction of PNP.
Gesehen am 12.04.2018